Sports injuries in brazilian blind footballers - Magno e Silva, M. P.; Morato, M. P.; Bilzon, J. L. J.; Duarte, E. (International Journal of Sports Medicine, 2013)
The purpose of this study was to assess the characteristics and prevalence of sports-related injuries in visually disabled athletes of the Brazilian football 5-a-side team. The participants were 13 male athletes, all classified as B1 visual class, members of the Brazilian team, who played in five consecutive international competitions. Data were collected using the Brazilian Paralympic Committee and the Brazilian Confederation of Sports for the Blind report form. From the total of 13 athletes, 11 succumbed to some form of injury during the 5 competitions, which incorporated 23 matches, representing a prevalence of 84.6%. A total of 35 sports injuries were recorded, giving a clinical incidence of 2.7 injuries per athlete and an injury risk of 0.85 and an incidence rate of 0.12 injuries per match. Traumatic injuries (80%) were more common than overuse injuries (20%) (p<0.05). The highest distribution of injury was in the lower limbs (80%), followed by the head (8.6%), spine (5.7%) and upper limbs (5.7%). The body regions most affected were the knee (28.6%), feet (17.1%), ankle (11.4%) and thigh (11.4%). Contusions (31.4%), sprains (25.7%) and tendinopathy (8.6%) were the most frequent diagnoses. This is the first study to describe the nature and prevalence of sports-related injuries in 5-a-side football in blind athletes. The results are important in guiding strategies to inform the implementation of preventive pathways and provide a strong rationale for the compulsory use of additional protective equipment.